Development of a classification (descriptive) system for a preference‐based quality of life measure for dental caries (dental caries utility index) among adolescents. (2nd December 2021) - Hettiarachchi, Ruvini M.; Kularatna, Sanjeewa; Byrnes, Joshua; Chen, Gang; Mulhern, Brendan; Scuffham, Paul A.
Abstract: Objectives: Preference‐based quality‐of‐life measures (PBMs) have been developed in many clinical areas to aid estimation of more accurate utility values for economic evaluations. Existing oral health‐related quality‐of‐life (OHRQoL) instruments are non‐PBM and hence, cannot be used to generate utility values. The objective of this study was to develop a classification system for a new PBM (dental caries utility index‐DCUI) for the most prevalent childhood oral health condition: dental caries. Methods: Possible domains and items to be included in the classification system were identified based on the reviewing available pediatric non‐PBM OHRQoL instruments, studies eliciting utility values for oral health outcomes and clinical dentistry textbooks and based on the findings, a draft classification system was developed. To refine the draft classification system, semi‐structured interviews were conducted among a convenience sample of 15 12–17‐year‐old adolescents who had experience with dental caries. The classification system was further refined and validated by a group of dental experts, using a modified Delphi technique. Results: The classification system comprised five items (pain/discomfort, difficulty in eating food/drinking, worried, ability to participate in activities, and appearance) and each item had a four‐level response scale. Conclusion: The classification system developed herein is considered an amenable tool for the subsequent development of a new PBM for dental caries. Once the scoring algorithm is completed, the classification system can be used to incorporate economic evaluations of dental caries health interventions.